Carotenoid content and retinol activity equivalents (RAE) of seven varieties of Mas Cotek (Ficus deltoidea) leaf extracts - ISMAIL, Azrina; Shahidan, Norshazila; Othman, Rashidi; MAR, NASHRIYAH (Science Publishing Corporation Inc, 2018)
Ficus deltoidea, also known as mistletoe fig or Mas cotek in Malay is believed to have health benefits due to the presence of bioactive compounds such as flavonoids and carotenoids. However, there are limited studies that show evidence of carotenoid compounds in Ficus deltoidea leaf extracts, especially in Malaysia. The aim of this study is to determine the carotenoid content of seven varieties of Ficus deltoidea leaf extracts and its retinol activity equivalent (RAE). Carotenoid content was identified by using High-Performance Liquid Chromatography (HPLC) and its RAE was determined by using a formula where 12μg of β-carotene is equivalent to 1 RAE. The carotenoids detected in seven varieties of Ficus deltoidea were lutein and β-carotene. The highest carotenoid content detected in Ficus deltoidea leaf extract was β-carotene which ranged from 14.25 ± 8.84 ug/ul (Ficus deltoidea var. deltoidea ) to 1612.00 ± 17.68 ug/ul (Ficus deltoidea var. angustifolia), while lutein content ranged from 23.00 ± 0.71 ug/ul (Ficus deltoidea var. deltoidea ) to 62.25 ± 0.35 ug/ul (Ficus deltoidea var. bilobata). The RAE found ranged from 171.00 ± 106.07 (var. deltoidea) up to 18726.00 ± 1080.87 (var. angustifolia). The data obtained from this study indicated that Ficus deltoidea leaves of different varieties had significantly different carotenoid contents. Thus, there is potential for Ficus deltoidea to be used as an alternative natural carotenoid source for food and pharmaceutical industries.